Respuesta :

9514 1404 393

Answer:

  (x, y) = (3, 7)

Step-by-step explanation:

If you divide the second equation by 2, it becomes ...

 -x +2y = 11

Adding this to the first equation gives you the value of y:

  (x -y) +(-x +2y) = (-4) +(11)

  y = 7 . . . . . . . . simplify

The first equation can be rearranged to give an expression for x:

  x = y -4

  x = 7 -4 = 3

Then the solution is seen to be (x, y) = (3, 7).

__

Personally, I like a graphing calculator for a quick and easy solution to many linear systems. (If the solutions are non-integers, it may not be so helpful.)

Ver imagen sqdancefan